John's error is assuming that any number to the zero power equals 1. This is only true for non-zero numbers.
Carol's error is in simplifying the exponents incorrectly.
The correct answer is:
(2^2 * 2^(-6)) - 3 * (2^0)
= 2^(2 + (-6)) - 3 * 1
= 2^(-4) - 3
= 1/2^4 - 3
= 1/16 - 3
= 1/16 - 48/16
= -47/16
Students were given the task to fully simplify:
(2^2.2^-6) -3 x (2)^0
John believes the answer was 1 as any number to the zero power (except 0^0) equals 1.
Carol believes that the answer is 4^12 since 2 x 2 = 4 and for the exponents 2 + -6 = -4 and -4 x -3 = 12
What is John's error?
What is Carol's error?
What is the correct answer. Show your work.
1 answer